The Measurement of Thermal Conductivity with Comparative Methods for Thermolectric Materials - Marifatin, Indah; Muntini, Melania S. (MJI Publisher by PT Mitra Jurnal Indonesia, 2023)
Research on the thermal conductivity of thermoelectric materials is still being carried out to control the flow of heat through the material so as to obtain a good thermoelectric material. The focus of this research was conducted to determine how to measure thermal conductivity using a comparative method, determine the value of the thermal conductivity of each sample, and determine the the effect of the porosity value on thermal conductivity. Measurements were made using variations of two types of materials, namely n-type Bi0.58Te1.42 and p-type Sb0.405Te0.595 and two sample sizes, namely (4×4×4) and (6×4×4) . The measurement of thermal conductivity using the comparative method, namely heater, thermocouple 1, aluminum metal, thermocouple 2, sempel, thermocouple 3 and heat sink are arranged in series to obtain data , , and for each increase in room temperature of 30 to 300 . The importance of low thermal conductivity in thermoelectric materials is to be efficient when converting the material. The data obtained through measurement are then used to calculate the value of thermal conductivity. Based on the results obtained in this study, the lowest thermal conductivity value is Bi0.58Te1.42 (4×4×4) at 4.12 . The thermal conductivity of the thermoelectric materials will be smaller at the smaller the porosity for each sample variation. In the sample Bi0.58Te1.42 (4×4×4) , the smallest porosity value was 0.087 %. So in this research a good thermoelectric material is Bi0.58Te1.42 (4×4×4) .